Hubungan antara Tanggung Jawab terhadap Tugas (Task Commitment) dan Disiplin Belajar dengan Hasil Belajar Mahasiswa - Firzanunnajik, Moh.; Afif, Nur (Lembaga Yasin AlSys, 2023)
The first, to analyze and find out the positive and significant relationship between the Task Commitment with learning outcomes. Second, to analyze and determine the positive and significant relationship between learning discipline and learning outcomes. Third, to analyze and determine the positive and significant relationship Task Commitment and learning discipline simultaneously with learning outcomes. This research design uses a quantitative approach with questionnaires to obtain, using secondary data, data in the form of a GPA, followed by deepening through interviews and direct observation to data sources. Postgraduate of the PTIQ for the Even Semester of the Academic a population. While the sampling in this study used a cluster sampling technique by taking even semester students for the 2021 academic year Masters Program in Islamic Education Management at the PTIQ. The results of this study are: First, there is a positive and significant relationship between task commitment and student learning outcomes the even semester of the 2021 academic year PTIQ with the level of dependence of task commitment on learning outcomes of 29.1%. Second, the relationship between learning discipline and learning outcomes for the even semester PTIQ has a positive and significant relationship. The level of dependence of learning discipline on learning outcomes of 26.8%. Third, the task commitment and learning discipline owned by students of the even semester of the 2021 academic year PTIQ jointly have a moderate relationship with learning outcomes. The level of dependence on learning discipline and task commitment together on learning outcomes of 29.5%.